Conference on the Current Status and Development of the Physician Assistant - Duke University. School of Medicine (1968)
Program from the October 28-29 PA conference at the Statler Hilton Inn in Durham, NC. Speakers include D. Robert Howard, E. Harvey Estes, Henry Weitz, Louis R. Pondy, Richard O. Cannon, Bill Stanhope, and Charles L. Hudson.